ANALISIS KETERAMPILAN MEMBACA PEMAHAMAN MELALUI MEDIA PEMBELAJARAN KOMIK DIGITAL CERITA RAKYAT SISWA KELAS III SD KABUPATEN MAGELANG - Winda Dwi Hudhana; Soleh Ibrahim; Irpa Anggriani Wiharja (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to analyze the reading comprehension skills of third-grade elementary school students through digital comic media based on folktales in Magelang Regency. This research is a qualitative descriptive study conducted in five elementary schools in Salaman District: SDN 1 Salaman, SD Muhammadiyah Tempuran, SD IT Laboratorium, SD Muhammadiyah Jetis, and SDN Ngadirejo. Data collection techniques included literature review, observation, test sheets, and documentation. The findings reveal that the reading comprehension skills of third-grade students in Salaman District still face challenges, particularly in reading fluency and learning motivation, which are crucial factors for comprehension. The use of digital comic media has been shown to improve students' reading comprehension skills, with achievement levels increasing from 69.5% to 88% after implementation, supported by enhanced motivation and active student participation. However, not all students experienced the same level of improvement, indicating the need for additional interventions such as learning support, tailored teaching methods, visual aids, and counseling services. The success of digital comics in learning demonstrates their potential as collaborative and contextual literacy media, supported by a conducive learning environment and parental involvement. Furthermore, a comfortable school environment and a literacy movement involving the entire school community reinforce students' literacy achievements.